Analisis Kepuasan Pelanggan Terhadap kualitas Pelayanan dengan Metode Servqual, Customer satisfaction Index dan Importance Performance Analysis pada Percetakan Dwi Jaya Mulia Gresik - Farid Andi Kusuma; Said Salim Dahda; Elly Ismiah (Departement of Mathematics Education, 2022)
In order for business owners to increase and maintain customer happiness, this study explores whether there are significant differences in perceptions and expectations of service quality. The author uses quantitative analysis. Data was collected through surveys and analyzed using IPA (Importance Performance Analysis), CSI, and Service of Quality (Customer Satisfaction Index) procedures. The survey findings show that, although customers are satisfied with the services provided, they are subpar. This is evidenced by the findings of a study on a customer satisfaction level of 82% as measured by CSI (Customer Satisfaction Index) techniques or procedures. Five qualities indicated in quadrant I (top priority) and four qualities indicated in quadrant II (maintain achievement), indicating outstanding service quality